Renoprotective effects of empagliflozin are linked to activation of the tubuloglomerular feedback mechanism and blunting of the complement system - Chen, Xin; Delić, Denis; Cao, Yaochen; Shen, Linghong; Shao, Qin; Zhang, Zheyu; Wu, Hongwei; Hasan, Ahmed A.; Reichetzeder, Christoph; Gaballa, Mohamed M. S.; Krämer, Bernhard; Klein, Thomas; et al. (American journal of physiology. Cell physiology, 2023)
Download figureDownload PowerPoint
Online veröffentlicht: 13. Februar, 2023
Gesehen am 19.03.2024